010. Ileus Obstruktif Letak Tinggi E.C Susp Hirschprung pada Pasien Umur 22 Tahun di RSUP Prof. Dr IGNG Ngoerah pada Tahun 2023 - Pandita, Made Bagus Ari; Sueta, Made Agus Dwianthara (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p010, 2024)
Background : Hirschsprung is a disease that occurs in the intestine, and cases most often appear in the colon (colon). Symptoms that usually arise are chronic constipation, failure to grow, and malnutrition. The surgical procedure approach that can be performed in this case is by carrying out an exploration laparatomy and placed a colostomy on the patient. Case : A 22-year-old male patient presents to the emergency department with abdominal pain, His pain began suddenly then dissappear gradually, accompanied by flatulence and nausea since a week ago. Other complaints such as fever and vomiting are denied. Patients with a history of defecation patterns every 2-3 days. Patients complain of difficulty defecating since last week before admitted, the stool form was a small amount of liquid, frequency is 2-3x/day. Stool with blood (-), black or tarry stool (-). Patients with a history of circumcision surgery. The results of the examination showed an increase in WBC 15.11. Based on the BOF results, the results described as a leading to paralytic ileus, Fecal material prominent as high as the pelvic cavum. In addition, based on the results of abdominal ultrasound, it is said that most of the scanning areas are covered by prominent intestinal gas, mild fatty liver. After the exploratory laparatomy, no signs of malignancy were found in the patient, but there was suspicion towards Hirschsprung where the patient did not have the flexura hepatica ligament and the lienalis flexura ligament. Conclusion: Hirschsprung requires surgical procedures that must be explained throughly to patient and families. The surgical procedure approach that can be performed in this case is by carrying out an exploratory laparatomy and the placed a colostomy on the patient. And colon in loop will be used to determine and evaluate the intestine height with aganglionic.